Magnetic nanoparticle - indium phthalocyanine conjugate embedded in electrospun fiber for photodynamic antimicrobial chemotherapy and photodegradation of methyl red - Azole Sindelo (Heliyon, 2019)
ClIn(III) octacarboxy phthalocyanine (ClInOCPc) when alone or conjugated to magnetic nanoparticles (MNP-ClInOCPc) was employed for both photodynamic antimicrobial chemotherapy of an unknown water sample and Staphylococcus aureus, and for photo-degradation of methyl red (MR). The singlet oxygen quantum yields (ΦΔ) in water using ClInOCPc and MNP-ClInOCPc embedded in polyacrylonitrile (PAN) electrospun fibers were 0.36 and 0.22, respectively. When in solution, MNP-ClInOCPc gave 90.6% photoinactivation of microbes in a water sample from the stream and of ClInOCPc resulted in 84.8 % photoinactivation. When embedded to the polymer, there was 48.0% clearance for ClInOCPc and 63.7% clearance for MNP-ClInOCPc for the microbes in the water sample from the stream. For the photo-degradation of MR, the rate of degradation increased with decrease of the MR concentration with the MNP-ClInOCPc having the fastest rate.